Verletzen sich Jungen beim Sport häufiger und anders als Mädchen? - Schneider, S.; Diehl, Katharina; Bruehmann, B. (Gesundheitswesen, 2012)
Representative data for Germany show that each year 7.7% (95% CI: 7.0-8.6%) of all children and adolescents suffer injuries in sport. The reasons are mainly collisions and falls. The most frequent consequences were injuries to the muscle-tendon apparatus and fractures. There were no significant differences, except for a few exceptions, between the genders for the relative risk of injury and regarding the injury pattern (cause, medical diagnosis, degree of severity). © Georg Thieme Verlag KG. Stuttgart-New York.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Adolescents; incidence; physical activity; risk; sports injuries